2015
DOI: 10.1016/j.cell.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Time for Food: The Intimate Interplay between Nutrition, Metabolism, and the Circadian Clock

Abstract: The circadian clock, a highly specialized, hierarchical network of biological pacemakers, directs and maintains proper rhythms in endocrine and metabolic pathways required for organism homeostasis. The clock adapts to environmental changes, specifically daily light-dark cycles, as well as rhythmic food intake. Nutritional challenges reprogram the clock, while time-specific food intake has been shown to have profound consequences on physiology. Importantly, a critical role in the clock-nutrition interplay appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
569
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 678 publications
(589 citation statements)
references
References 78 publications
7
569
0
13
Order By: Relevance
“…2H and Fig. S6H), even though Bmal1 is known to control its circadian expression (4,5). Instead, we found that these NAMPT increases were related to an increased CREB binding to a CRE DBS (TGACGTCA) located in the NAMPT promoter (Fig.…”
Section: An Increased Glucagon Secretion Results In An Activation Of mentioning
confidence: 74%
See 1 more Smart Citation
“…2H and Fig. S6H), even though Bmal1 is known to control its circadian expression (4,5). Instead, we found that these NAMPT increases were related to an increased CREB binding to a CRE DBS (TGACGTCA) located in the NAMPT promoter (Fig.…”
Section: An Increased Glucagon Secretion Results In An Activation Of mentioning
confidence: 74%
“…Numerous studies have shown that under homeostatic conditions, the functions of PCCs and metabolism are tightly linked and that perturbations in their interactions leads to pathologies, e.g., obesity and metabolic syndrome (3)(4)(5).The identity of some of the molecular pathways that couple PCCs to metabolism are known (3)(4)(5), but it is largely unknown how environmental cues, e.g., altered feeding schedules, may directly perturb the expression of individual CC components (5-7), thereby leading to obesity and a metabolic syndrome-like pathology (5). Assuming that specific metabolic perturbations generated by switching the feeding time could selectively affect the time of expression of some of the CC core components, we looked for both metabolic and PCC alterations at early RF times.…”
mentioning
confidence: 99%
“…In addition to SIRT1, other redox-sensing nuclear proteins are likely to be affected by intranuclear organization of NADH metabolism. Among these proteins, BMAL1 and NPAS2/CLOCK are β-HLH-PAS domain-containing transcription factors, which heterodimerize and drive the expression of circadian genes (54). This notion is relevant, because SIRT1 modulates circadian gene expression (6,9,19).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular oscillator consists of interconnected transcriptional and translational feedback loops, in which multiple layers of control, including temporal posttranscriptional and posttranslational regulation, play important roles (5). These additional layers of regulation are largely coordinated by systemic cues originating from circadian clock and/or feeding-coordinated rhythmic metabolism, allowing the adjustment of the molecular clockwork with the metabolic state of the cell (6). During the last decades, efforts have been made to produce a comprehensive knowledge of the transcriptional regulation orchestrated by the circadian clock (7)(8)(9) and feeding rhythms (10,11).…”
mentioning
confidence: 99%